Pemanfaatan Media Sosial dalam Pemasaran Digital - Heri Prabowo; Sutrisno Sutrisno; Henry Casandra Gultom; Puji Lestari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Micro, Small and Medium Enterprises (MSMEs) have a very important role in the Indonesian economy. Among its important roles is being able to absorb labor and encourage economic growth. The development of social media in Indonesia has shown very rapid growth in recent years. Due to the important role of MSMEs and the rapid development of social media, MSME players feel the need to utilize social media for digital marketing activities. Activities are carried out by providing understanding and training on the use of social media. From the activities that have been carried out, it shows that there is an understanding of social media and its use in the hope of attracting potential buyers which will have an impact on increasing the sales turnover of MSMEs.